Study protocol for SeniorWorkingLife - push and stay mechanisms for labour market participation among older workers - Lars Louis Andersen; Emil Sundstrup (BMC, 2019)
Abstract Background Due to demographic changes across Europe there are strong political interests in maintaining the labour force by prolonging working life, i.e. increasing retirement age. This may pose both challenges and opportunities for societies, workplaces, and individuals. The SeniorWorkingLife (Danish: SeniorArbejdsLiv) project investigates push and stay mechanisms for labour market participation - now and in the future - among older workers (≥50 years). Methods In July 2018, 30,000 Danes age 50 or older (18,000 employed, 7000 unemployed, 3000 voluntary early retirements, 2000 disability pensions) were invited to participate, of which 15,721 (52.4%) replied to the entire questionnaire and 17,885 (59.6%) replied at least in part. Baseline data collection was terminated in October 2018. The questionnaire covers 14 domains in relation to push and stay mechanisms for labour market participation: 1) basic information (demographics, employment status etc.), 2) multiple-choice question covering a wide range of push and stay mechanisms, 3) role of the workplace, 4) age-discrimination, 5) personal economy, 6) possibility for voluntary early retirement among employed and unemployed, 7) gradual retirement, 8) competencies and continued education, 9) return-to-work, 10) new technologies at the workplace, 11) job satisfaction and well-being, 12) working environment, 13) lifestyle, 14) health and functional capacity. The project aspires to repeat the survey as a prospective cohort every 2-3 years and to perform longitudinal follow-up in Danish high-quality registers about work and health. Discussion The SeniorWorkingLife project will provide important knowledge about push and stay mechanisms for labour market participation among older workers. Push refers to mechanisms that increase the risk of premature exit from the labour marker, e.g. due to poor health, poor working environment, age discrimination, and stay to mechanisms prolonging working life e.g. due to attractive working conditions and a good working environment. The project will also to some degree investigate stuck, pull and jump mechanisms. Collaboration and use of the data for scientific purposes by other researchers are encouraged. Interested researchers should contact the corresponding author. Trial Registration Registered as cohort study in ClinicalTrials.gov Identifier NCT03634410 (August 16, 2018).